GNOSEOLOGICAL ANALYSIS OF HISTORICAL CONSCIOUSNESS IN THE CONTEXT OF NATIONAL CONSCIOUSNESS (Scientific journal of the Fergana State University, 2024)
This article presents a comparative study of philosophical views on the epistemological analysis of historical consciousness in the context of national identity. National identity is also determined by the historical development of historical consciousness, research based on the social context.